The physiological consequences of acceleration during shuttle running - Akenhead, R.; French, D.; Thompson, K. G.; Hayes, P. R. (International Journal of Sports Medicine, 2015)
This study examined the acceleration demands associated with changing direction and the subsequent physiological consequences of acceleration during running at 3 submaximal speeds. 10 male professional footballers completed four 600?m running bouts at 3 speeds (2.50, 3.25 & 4.00?m·s-1). Each bout was in the format of either: i) 3 laps of a 200 m track (CON), ii) ten 60 m shuttles (S60), iii) twenty 30 m shuttles (S30), or iv) thirty 20 m shuttles (S20). Peak heart rate (HRPEAK), blood lactate concentration (BLa) and RPE (Borg CR-10) were recorded for each bout. A single change of direction required 1.2, 1.5 and 2.0 s of acceleration at running speeds of 2.50, 3.25 and 4.00 m s-1 respectively. An increase in time spent accelerating produced a linear increase in BLa (r=0.43-0.74) and RPE (r=0.81-0.93) at all speeds. Acceleration increases linearly with change of direction frequency during submaximal shuttle running. Increased time spent accelerating elicits proportional increases in perceived exertion, BLa and HRPEAK. The current study further underlines the need to consider acceleration when quantifying training load during activities involving numerous changes of direction.